1981
DOI: 10.1021/bi00522a008
|View full text |Cite
|
Sign up to set email alerts
|

Guanidine hydrochloride induced unfolding of yeast iso-2 cytochrome c

Abstract: The properties of the guanidine hydrochloride induced unfolding transition of iso-2 cytochrome c (iso-2) from Saccharomyces cerevisiae have been investigated by using kinetic and equilibrium techniques and have been compared with previously published studies of horse cytochrome c, which differs from iso-2 by 46% in amino acid sequence. Measurements of absorbance in the ultraviolet and visible spectral regions as a function of guanidine hydrochloride concentration give superimposable equilibrium transition curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
81
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 38 publications
6
81
0
Order By: Relevance
“…However, throughout the entire unfolding branch of the T~ kinetic phase, unfolding of N52I iso-2 is much slower than unfolding of iso-2. The iso-2 kinetic data presented in Figures 6 and S1 (supplementary material) are in good agreement with previous results (Nall & Landers, 1981;Nall, 1983;Osterhout & Nall, 1985;Nall et al, 1988). The rate of slow phase (T~,,) fluorescence-detected aThe fluorescence equilibrium unfolding parameters for iso-2 and N52I iso-2, at 20°C, 0.1 M sodium phosphate, pH 6.0, and protein concentrations of 4.1 pM.…”
Section: Folding/unjolding Kineticssupporting
confidence: 88%
See 2 more Smart Citations
“…However, throughout the entire unfolding branch of the T~ kinetic phase, unfolding of N52I iso-2 is much slower than unfolding of iso-2. The iso-2 kinetic data presented in Figures 6 and S1 (supplementary material) are in good agreement with previous results (Nall & Landers, 1981;Nall, 1983;Osterhout & Nall, 1985;Nall et al, 1988). The rate of slow phase (T~,,) fluorescence-detected aThe fluorescence equilibrium unfolding parameters for iso-2 and N52I iso-2, at 20°C, 0.1 M sodium phosphate, pH 6.0, and protein concentrations of 4.1 pM.…”
Section: Folding/unjolding Kineticssupporting
confidence: 88%
“…One test for structural and energetic similarity between the folding transition state and the native conformation is the relationship between equilibrium free energies and activation free energies of folding (Matouschek & Fersht, 1993;Matthews & Fersht, 1995). Tests for a relationship between stability and folding rates for cytochromes c have compared the kinetics of folding of yeast is0 cytochromes c (Nall & Landers, 1981;Mines et al, 1996) to the folding kinetics of the more stable horse cytochrome c (Ikai et al, 1973;Tsong, 1976).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The control strain, B-7533, has the same genotype, except the wild-type CYCl + gene is present. Protein was purified by a variation on methods described previously (Sherman et al, 1968;Nall & Landers, 1981).…”
Section: Yeast Strains Mutagenesis and Protein Purificationmentioning
confidence: 99%
“…Mitochondrial c-type cytochromes are among the best characterized proteins. Several species have been studied by X-ray crystallography [12][13][14] , and extensive protein-folding studies have been reported [15][16][17][18][19][20][21] . …”
mentioning
confidence: 99%